Pursuit of passionate purpose : - Szczurek, Theresa M. (John Wiley & Sons, Inc., 2005)
The author, a corporate executive turned consultant, offers a practical guide for producing extraordinary results and reaping the real rewards of life by caring passionately about what we desire and then pursuing it with true determination. She advises the need to build relationships and the importance of maintaining supportive friendships. With extensive research involving 80 participants, she offers her proven process for living life fully through self-assessment, determining what we do and do not want, establishing how to get what we want, and evaluating our progress while making adjustments. Her six success strategies include honoring opposites in life, surrendering to the natural flow of life without attachment to a certain outcome, and discovering what energizes and what discourages us so we can focus on the former and distance ourselves from dispiriting people and situations. This how-to road map may be helpful to a broad range of library patrons who are searching for enrichment and purpose in their lives